Audit Committee and Audit Quality Reduction Behavior (A Literature Study) - Wiwiek Winarta; Nurmala Ahmar (Greenation International Journal of Economics and Accounting, 2024)
This study aims to review the literature related to the impact of audit committee characteristics on audit quality and identify research gaps in this area. The phenomenon of audit-quality reduction behavior is a significant issue in the audit world, where this behavior can reduce the quality of the resulting audit. This study reveals that audit committee characteristics such as committee size, frequency of meetings, and financial expertise of members play an important role in determining the resulting audit quality. The findings show that larger audit committees that meet more frequently tend to produce higher quality audits. In addition, the financial expertise of audit committee members has been proven to improve the committee's ability to detect and prevent errors or fraud in financial statements. This study also supports the Theory of the Firm which states that the main objective of the firm is to maximize value for shareholders by minimizing agency costs and increasing operational efficiency. These findings have important implications for the development of better corporate governance policies and practices.